2018
DOI: 10.1039/c8ee00278a
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state-ligand-exchange free quantum dot ink-based solar cells with an efficiency of 10.9%

Abstract: Solid-state-ligand-exchange free high-efficiency colloidal quantum dot solar cells were developed by direct coating of n-type and p-type quantum dot inks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(126 citation statements)
references
References 47 publications
2
124
0
Order By: Relevance
“…Efficient PbS QD devices have been demonstrated with solution-phase ligand treatments using lead halides 1,2 and 3-mercaptopropionic acid (MPA). 23 In contrast, the few perovskite QD solar cells reported to-date still require a layer-by-layer ligand treatment using a lead nitrate (Pb(NO 3 ) 2 ) solution in methyl acetate (MeOAc). 3,4 In this work, we analyze the cost of leading PbS and CsPbI 3 perovskite QD synthesis and ink preparation methods, guided by direct commercial experience with high-volume QD production.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient PbS QD devices have been demonstrated with solution-phase ligand treatments using lead halides 1,2 and 3-mercaptopropionic acid (MPA). 23 In contrast, the few perovskite QD solar cells reported to-date still require a layer-by-layer ligand treatment using a lead nitrate (Pb(NO 3 ) 2 ) solution in methyl acetate (MeOAc). 3,4 In this work, we analyze the cost of leading PbS and CsPbI 3 perovskite QD synthesis and ink preparation methods, guided by direct commercial experience with high-volume QD production.…”
Section: Introductionmentioning
confidence: 99%
“…[5] It has been shown that a significant improvement in QD PV performance can be achieved if the deposited PbS QD films are chemically treated to undergo ligand exchange, replacing OA with shorter ligands, such as halides and short-chain thiols, which leads to high charge conductivities within QD films, boosting the power conversion efficiency of QD PVs. [1][2][3][4] This ink can then be deposited on a substrate to form the QD PV device active layer, [1][2][3][4] with recently reported PbS QD PVs achieving 12% power conversion efficiency (PCE). In a separate synthetic step, OAcapped PbS QDs are exchanged with short ligands in solution and then suspended at a high concentration in a solvent to form an ink.…”
mentioning
confidence: 99%
“…[1][2][3][4] This ink can then be deposited on a substrate to form the QD PV device active layer, [1][2][3][4] with recently reported PbS QD PVs achieving 12% power conversion efficiency (PCE). [9][10][11] For example, the leading PbS QD ligand exchange procedures employing lead halides such as lead(II) bromide [1][2][3] and lead(II) iodide [1][2][3][4] have yet to be evaluated with regards to U.S. Environmental Protection Agency and European Union regulatory limits.In this study, we present a solution-phase ligand exchange method that reduces the amount of utilized lead by employing tetrabutylammonium iodide (TBAI) as the source of iodide ligands. A recent report by Jean et al revealed that current solutionphase QD ligand exchange methods create an added cost of $6.30 g −1 of QDs, an expense that negatively impacts the commercial viability of QD PV modules.…”
mentioning
confidence: 99%
See 2 more Smart Citations